2006
DOI: 10.1073/pnas.0603429103
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the mechanical properties of isolated tectorial membrane using atomic force microscopy

Abstract: The tectorial membrane (TM) is an extracellular matrix situated over the sensory cells of the cochlea. Its strategic location, together with the results of recent TM-specific mutation studies, suggests that it has an important role in the mechanism by which the cochlea transduces mechanical energy into neural excitation. A detailed characterization of TM mechanical properties is fundamental to understanding its role in cochlear mechanics. In this work, the mechanical properties of the TM are characterized in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 37 publications
6
67
3
Order By: Relevance
“…Whereas von Békésy (1953Békésy ( , 1960 and Shoelson et al (2004) found no systematic longitudinal stiffness changes in the TM, a systematic change in driving point stiffness measured at the TM has been reported by our group in the gerbil (Emadi et al 2002;Richter et al 2007) and by Gueta at al. (Gueta et al 2006 in the mouse.…”
Section: Tectorial Membranementioning
confidence: 44%
See 3 more Smart Citations
“…Whereas von Békésy (1953Békésy ( , 1960 and Shoelson et al (2004) found no systematic longitudinal stiffness changes in the TM, a systematic change in driving point stiffness measured at the TM has been reported by our group in the gerbil (Emadi et al 2002;Richter et al 2007) and by Gueta at al. (Gueta et al 2006 in the mouse.…”
Section: Tectorial Membranementioning
confidence: 44%
“…(Gueta et al 2006 in the mouse. Gueta et al's (2006) published data on TM Young's modulus differed significantly from previously reported values (Gueta et al 2006(Gueta et al , 2008(Gueta et al , 2011. They measured Young's modulus using an atomic force microscope probe and demonstrated that the values decrease from base to apex by about TEUDT AND RICHTER: Basilar Membrane and Tectorial Membrane Stiffnessan order of magnitude (210 to 24 kPa) and vary along the radial axis by a factor of two.…”
Section: Tectorial Membranementioning
confidence: 86%
See 2 more Smart Citations
“…In the mammalian cochlea the Young's modulus of the tectorial membrane has been estimated and exhibits a gradient of tectorial stiffness (33)(34)(35)(36)(37). Values reported range from E ϭ 0.3 kPa at the apex to 3 kPa at the base in gerbil (37) and from E ϭ 24 kPa at the apex to 224 kPa at the base in mouse (36).…”
Section: Discussionmentioning
confidence: 99%